Pengaruh Health Education dengan Leaflet terhadap Pengetahuan Ibu Hamil tentang 1000 Hari Pertama Kehidupan di RSUD K.H. Hayyung Kabupaten Kepulauan Selayar - Anwar, Suwarni; Akib, Resky Devi; Ariyana, Ariyana (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
The first 1000 days of life is a crucial period in determining the nutritional status and growth and development of children. Pregnant women's lack of knowledge about nutrition during this time can increase the risk of stunting. The purpose of this research is to determine the influence of health education with leaflets on pregnant women's knowledge about the first 1000 days at K.H. Hayyung Hospital. This research method used a quasi-experiment with a population of 138, and a sample of 58 pregnant women divided into 29 control groups and 29 intervention groups. This type of data collection research uses interviews with questionnaires. Data analysis used univariate analysis, prerequisite analysis with normality test and homogeneity test, and bivariate analysis with paired sample t-test and independent sample t-test. The results of the independent sample t-test in this study obtained a significant value of 0.002 < 0.05 which means that there is a significant difference between the control group and the intervention group which means that H0 is rejected and H1 is accepted. H1 states that there are significant differences between the two groups. In conclusion, there is an influence of health education with leaflets on pregnant women's knowledge about the first 1000 days of life at K.H. Hayyung Hospital, Selayar Islands Regency. This intervention can be applied as an educational strategy in health care facilities to prevent stunting from the get-go.